DFT Calculations of Silver Atom Modified Tungsten Disulfide Monolayer as Promising Sensing Materials for Small Molecular Toxic Gases - Qi Zhao; Jin He; Songyuan Li; Suya Li; Qi Ning; Hao Cui (Applied Sciences, 2023)
In the contemporary context, the significance of detecting harmful gases cannot be overstated, as it profoundly affects both environmental integrity and human welfare. In this study, theoretically, density functional theory was employed to explore the adsorption behavior of three prevalent hazardous gases, namely CO, NO2, and SO2, on silver-atom-modified tungsten disulfide (WS2) monolayer. The multifaceted analysis encompasses an array of critical aspects, including the adsorption structure, adsorption energy, electron transfer, and charge density difference to unravel the adsorption behavior. Further exploration of electronic properties encompassing band structure, density of states (DOS), and work function was conducted. The ambit of our exploration extends to the desorption properties based on adsorption-free energies. Among these gas molecules, NO2 stands out with the highest adsorption energy and the most substantial electron transfer. Notably, each of these adsorption processes triggers a redistribution of electron density, with NO2 exhibiting the most pronounced effect. Furthermore, the adsorptions of CO, NO2, and SO2 induce a noteworthy reduction in the band gap, prompting the reconfiguration of molecular orbitals. Additionally, the adsorption of these gases also leads to an increase in the work function of Ag-WS2 to a different extent. Our investigation of desorption properties uncovers that Ag-WS2 can adeptly function at ambient temperatures to detect CO and SO2. However, for NO2 detection, higher temperatures become imperative due to the necessity for poison removal. The implications of our findings underscore the tremendous potential of Ag-WS2 as a sensing material for detecting these hazardous gases. Our research extends to the broader realm of surface modification of transition metal dichalcogenides and their promising applications in the domain of gas sensing.